Axiological Dimensions of Elementary School Teachers' Language Attitudes Towards Indonesian in Ciomas District - Hidayat, Bayu; Agustin, Mubiar (International Conference on Elementary Education, 2024)
The development of a positive attitude towards Indonesian to students is carried out at least by teachers who also have a positive attitude towards Indonesian. This study aims to observe the language attitudes of elementary school teachers at SD Negeri Parakan 01 towards Indonesian. This research is a qualitative research using case study method. Data collection is done through observation and interviews. Observations andinterviewswere conducted with 13 teachers consisting of 5 male teachers and 8 female teachers at SD Negeri Parakan 01, Ciomas District, Bogor. This study found that teachers at SD Negeri Parakan 01 had a positive attitude towards Indonesian, especially in terms of writing. Although it was found to have a positive attitude towards standard written Indonesian, in the teacher's writing they still showed insufficient in applying linguistic aspects.